The effect of probiotics and polysaccharides on the gut microbiota composition and function of weaned rats. Issue 3 (9th March 2018) - Wang, Mengxia; Chen, Yongxiong; Wang, Yuanyuan; Li, Yuan; Zheng, Haihui; Ma, Fangli; Ma, ChungWah; Zhang, Xiaojun; Lu, Biyu; Xie, Zhiyong; Liao, Qiongfeng
Abstract : A combination of probiotics and polysaccharides may be used as a functional food to modulate the composition and function of gut microbiota. Abstract : Weaning is an essential and important event for infants and rodent animals, and the dietary supplementation plays a crucial role in regulating the composition and function of gut microbiota in the initial period after weaning. In this study, we investigated the potential effects of two probiotics along with three polysaccharides (PP) in weaned rats. Male SD rats, 21 days of age, were divided into two groups: one group was administered with PP for four weeks and the other was not. Body weight, food intake, gut epithelial barrier function, digestive enzyme activities, and the composition and function of gut microbiota were analyzed. The dietary PP increased the body weight and food intake, promoted gut epithelial barrier integrity, and elevated the activities of digestive enzymes. Moreover, the microbial community structure was different between the two groups. At the genus level, Bifidobacterium, Lactobacillus, and Allobaculum were significantly increased, whereas Anaerostipes, Enterococcus, and Parabacteroides were observably reduced. Furthermore, PP significantly increased amino acid metabolism, energy metabolism, and SCFA-related metabolism. This study shows that synbiotics containing probiotics ( L. acidophilus NCFM and B. lactis Bi-07) in combination with polysaccharides (LBP, PCPs, and Lentinan) can modulate the composition of gut microbiota, stimulate the maturation of gut microbiota biological function, and promote the growth performance in weaned rats.